Sex differences in dynamic closed kinetic chain upper quarter function in collegiate swimmers - Butler, R.; Arms, J.; Reiman, M.; Plisky, P.; Kiesel, K.; Taylor, D.; Queen, R. (Journal of Athletic Training, 2015)
Context: Upper quarter injuries have a higher incidence in female swimmers; however, to date, there are few ways to assess the basic functional ability of this region. The upper quarter Y balance test (YBT-UQ) may assist in this process because it was developed to provide a fundamental assessment of dynamic upper quarter ability at the limit of stability.